Candidiasis and Mechanisms of Antifungal Resistance - Bhattacharya, Somanon (Antibiotics (Basel), 2020)
Candidiasis can be present as a cutaneous, mucosal or deep-seated organ infection, which is caused by more than 20 types of Candida sp., with C. albicans being the most common. These are pathogenic yeast and are usually present in the normal microbiome. High-risk individuals are patients of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), organ transplant, and diabetes. During infection, pathogens can adhere to complement receptors and various extracellular matrix proteins in the oral and vaginal cavity. Oral and vaginal Candidiasis results from the overgrowth of Candida sp. in the hosts, causing penetration of the oral and vaginal tissues. Symptoms include white patches in the mouth, tongue, throat, and itchiness or burning of genitalia. Diagnosis involves visual examination, microscopic analysis, or culturing. These infections are treated with a variety of antifungals that target different biosynthetic pathways of the pathogen. For example, echinochandins target cell wall biosynthesis, while allylamines, azoles, and morpholines target ergosterol biosynthesis, and 5-Flucytosine (5FC) targets nucleic acid biosynthesis. Azoles are commonly used in therapeutics, however, because of its fungistatic nature, Candida sp. evolve azole resistance. Besides azoles, Candida sp. also acquire resistance to polyenes, echinochandins, and 5FC. This review discusses, in detail, the drug resistance mechanisms adapted by Candida sp.